Seasoned - Mendes, Wency (InTensions, 2018)
Changing human consumption patterns and sustenance have always created new ripples of change. Be it food for our bodies, or material for industries – all progress via trade, barter, exchange and securities has been founded on systems of creating excess. Tea traveled the world and so did coffee and cocoa. Indian food may well be synonymous with chili, but chili was not indigenous to India, nor was the potato or tomato. But then, nothing belongs to any one region any more. Food has traveled from its regions of origin by conquests of colonization or peaceful trade. Yet, what we cook: does it ‘belong’ to us? Do its flavors? Or does it belong to memories, cohabiting with all that lives there: childhood games to see who could shell the most peas, moist kitchen floors, the first time you saw blood, and the lavish spread of both birthdays and Tehravin? What was it for you? How does food tell your story? Whose stories does it tell as it travels from Gujarat, Manipur, Kashmir, Dantewada to the meal you are here invited to share?